Design and optimisation of swirl pipes and transition geometries for slurry transport - Ariyaratne, Chanchala (2005)
This thesis is primarily concerned with the design and optimisation of transition ducts for lobed swirl-inducing pipes. Single-phase swirl-inducing pipe flows were modelled and optimised using Computational Fluid Dynamics (CFD). Optimised pipes were manufactured using rapid prototyping and an experimental investigation examines their effect on settling slurries of different densities.